FACTORS INFLUENCING THE FAILURE OF EXCLUSIVE BREASTFEEDING IN SRI DAMAI VILLAGE MUSI BANYUASIN REGENCY SOUTH SUMATRA PROVINCE IN 2024 - Henny, Henny Apriana; Vivi Restiyani Hasibuan; Dyanti SR Butarbutar; Eka Purnama Sari; Regita Aprianda; Nova Isabella Mariance Napitupulu, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Exclusive breastfeeding plays a crucial role in reducing infant mortality and promoting optimal child growth and development. Despite its importance, the rate of exclusive breastfeeding in Indonesia remains low, including in Sri Damai Village. Several factors such as maternal age, education, occupation, parity, knowledge, and family support are thought to influence the success of exclusive breastfeeding. Research objective: This study aims to comprehensively identify the various factors that contribute to the failure of exclusive breastfeeding in Sri Damai Village. These factors may include sociodemographic conditions, cultural beliefs, maternal knowledge and attitudes, family support, and the role of healthcare services. Methode: his research is a quantitative study with a cross-sectional design. The sample consisted of 34 mothers with infants aged 0–6 months in Sri Damai Village. Data were collected using a structured questionnaire and analyzed using the Chi-Square test. Research results: The study found that the failure of exclusive breastfeeding in Sri Damai Village was influenced by several key factors. Mothers aged 20–35 years made up 58.8% of cases, showing that being in the ideal reproductive age does not ensure successful breastfeeding. Statistical analysis confirmed significant relationships between all these variables and exclusive breastfeeding failure (p < 0.05). Conclusion and suggestion: The failure of exclusive breastfeeding in Sri Damai Village is influenced by several factors, with lack of family support and poor application of maternal knowledge being the most significant. Keywords: Exclusive Breastfeeding, Failure, Maternal Knowledge, Family Support, Contributing Factors